2022
DOI: 10.36628/ijhf.2021.0041
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Edge-to-Edge Mitral Valve Repair for Functional Mitral Regurgitation

Abstract: The presence and severity of functional mitral regurgitation (FMR) is associated with worse outcomes in patients with heart failure and reduced ejection fraction. Prior to the availability of percutaneous mitral valve repair, management for FMR has been limited to medical therapy, cardiac resynchronization therapy for a specific subset of patients and surgery which has yet to demonstrate mortality benefits. Transcatheter edge-to-edge repair (TEER) of the mitral valve has emerged in the past decade as an invalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…12 The development of the MitraClip G4 system with 4 different clip sizes and the introduction of CGA allows independent grasping of the leaflets instead of simultaneous grasping in challenging scenarios, such as severely restricted and tethered posterior leaflets. 13 In patients undergoing mitral TEER, especially with continuous LA pressure monitoring, a mean LA pressure of ≤15 mm Hg and mild or no residual MR are associated with better survival, lower HF hospitalizations, and improved symptoms. 14 The post hoc analysis of the COAPT trial showed that patients with lower serum creatinine and Kansas City Cardiomyopathy Questionnaire Overall Summary Score and treatment assignment to TEER with MitraClip plus GDMT have a better therapeutic response within 12 months than GDMT alone and these patient groups have ≤1+ residual MR and a significant reduction in right ventricular systolic pressure at 30 days.…”
Section: Optimizing Procedural Efficiency Of Teer In Smrmentioning
confidence: 96%
See 1 more Smart Citation
“…12 The development of the MitraClip G4 system with 4 different clip sizes and the introduction of CGA allows independent grasping of the leaflets instead of simultaneous grasping in challenging scenarios, such as severely restricted and tethered posterior leaflets. 13 In patients undergoing mitral TEER, especially with continuous LA pressure monitoring, a mean LA pressure of ≤15 mm Hg and mild or no residual MR are associated with better survival, lower HF hospitalizations, and improved symptoms. 14 The post hoc analysis of the COAPT trial showed that patients with lower serum creatinine and Kansas City Cardiomyopathy Questionnaire Overall Summary Score and treatment assignment to TEER with MitraClip plus GDMT have a better therapeutic response within 12 months than GDMT alone and these patient groups have ≤1+ residual MR and a significant reduction in right ventricular systolic pressure at 30 days.…”
Section: Optimizing Procedural Efficiency Of Teer In Smrmentioning
confidence: 96%
“…12 The development of the MitraClip G4 system with 4 different clip sizes and the introduction of CGA allows independent grasping of the leaflets instead of simultaneous grasping in challenging scenarios, such as severely restricted and tethered posterior leaflets. 13…”
Section: Optimizing Procedural Efficiency Of Teer In Smrmentioning
confidence: 99%
“…Pacientes com RM desproporcionalcom RM grave que não pode ser explicada pela gravidade da dilatação do VEdevem ser diferenciados daqueles com RM proporcional, pois não respondem satisfatoriamente às terapias médicas 65 . O reparo transcateter da válvula mitral borda a borda (TEER) para RM é a opção terapêutica no caso de sintomas persistentes após PCDT nesses pacientes 66 . No estudo Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patient with Functional Mitral Regurgitation (COAPT) 67 , a maioria dos pacientes inscritos apresentava RM desproporcional, com apenas 10% dos pacientes com RM proporcional apresentando índice de volume diastólico final do VE >96 mL/m 2 e área efetiva do orifício regurgitante ≤30 mm2.…”
Section: Reparo Da Válvula Mitral Transcateter Borda a Bordaunclassified
“…The MV repair "edge-to-edge" developed more than 30 years ago has found wide application in MV surgery, including in the treatment of ischemic MR (24). The "edge-to-edge" MV repair (Fig.…”
Section: Repair "Edge-to-edge"mentioning
confidence: 99%